Association between Foot Posture Asymmetry and Static Stability in Patients with Knee Osteoarthritis: A Case-Control Study. (6th June 2020) - Chen, Zehua; Shen, Zhen; Ye, Xiangling; Wu, Jiatao; Wu, Huai; Xu, Xuemeng
Abstract : Background . Interlimb asymmetries are considered to be closely related to knee osteoarthritis (KOA), but foot posture asymmetries in patients with KOA are scarcely reported. Objectives . We aimed to explore the asymmetrical difference in foot posture between the healthy adults and KOA patients and the relationship between foot posture asymmetry and static stability. Methods . 21 subjects suffering from KOA in the patient group (PG) and 21 healthy adults in the control group (CG) were included in this study. Foot postures on both feet were evaluated by using the foot posture index (FPI); subsequently, asymmetrical FPI scores between two feet were calculated for the two groups. Meanwhile, all the participants were tested with a standing on Dynamic and Static Balancing Instrument (Pro-kin 254P, TecnoBody Company, Italy) for bilateral stability assessment, and center of pressure (COP) parameters including sway length (SL, mm) and sway area (SA, mm 2 ) were recorded. Results . Compared to CG, a larger percentage of supinated feet was examined in relatively severe legs (5, 23.81%), relatively moderate legs (4, 19.05%), and merged results (9, 21.43%) of PG (P < 0.05 ), and the percentage of severe asymmetry (38.1%) was higher in the PG (P < 0.05 ). Moreover, these relationships between the absolute value of asymmetry score and SL or SA were significant in CG and PG, the P values below 0.01. Conclusions . Foot posture asymmetry is significantly associated with static stability both in KOA patients and healthy adults, and more severe asymmetry in foot posture was observed in KOA patients, so it is critical to evaluate foot posture asymmetry for treatment and rehabilitation for patients with KOA.